ChemInform Abstract: Zinc‐Catalyzed Enantioselective Electrophilic Amination of β‐Ketocarbonyl Compounds with Axially Chiral Phenanthroline Ligands. Issue 26 (June 2016) - Naganawa, Yuki; Komatsu, Hiroyuki; Nishiyama, Hisao
Abstract: Zinc‐catalyzed asymmetric α‐amination of various cyclic β‐ketocarbonyl compounds using azodicarboxylate (II) as the electrophilic nitrogen source is described.